Digital Policing ; Studi Pemanfaatan Teknologi Dalam Pelaksanaan Tugas Intelijen Kepolisian untuk Mencegah Kejahatan Siber (Cybercrime) - Ismail, Marzuki (Sekolah Tinggi Ilmu Kepolisian, 2023)
After the sociological transformation of society to a digital society with the support of the internet network, most behavioural habits, culture have also changed. Including financial transactions that used to be carried out conventionally since the last decade using various application platforms. Various crimes, especially online fraud crimes, are increasingly threatening and increasing significantly with various modus operandi that change and continue to develop. The development of digital technology has not been maximally utilised by police intelligence to prevent various forms of crime. Police intelligence has not used digital technology to the fullest to collect information and conduct digital data collection. This has resulted in slow anticipation of various potential cyber crimes. Digital policing in the implementation of police intelligence tasks needs to be continuously developed by investing in the latest technological equipment in order to realise a predictive, responsive and transparent police force with justice.The approach in this research is qualitative research with a literature study method by analysing books, journals, media news related to the use of technology in police intelligence tasks.